Pengaruh Persepsi Kepercayaan, Persepsi Risiko, dan Persepsi Kemudahan Penggunaan terhadap Niat Pembelian secara Online pada Konsumen di Kota Bengkulu - Dian Nursea; Islamuddin Islamuddin (Jurnal Ekonomi, 2022)
The purpose of this study was to determine the effect of perceived trust, perceived risk, and perceived ease of use on online purchase intentions on consumers in Bengkulu City. This research was conducted on consumers in Bengkulu City. The population of this research is consumers in Bengkulu City, while the sample of this research is Bengkulu City community totaling 170 people. Data collection techniques using observation, interviews, questionnaires. Data Analysis Techniques using Descriptive Analysis, Inferential Analysis It can be concluded that all variables Perception of Trust, Perception of Risk, and Perception of Ease of Use partially or simultaneously affect the Online Purchase Intention of Consumers in Bengkulu City.